Mechanisms of action of extracellular miRNAs - A.E. Abaturov; V.L. Babуch (Zdorovʹe Rebenka, 2022)
The mechanisms of action of extracellular miRNAs are given in the scientific review. To write the article, information was searched using Scopus, Web of Science, MedLine, PubMed, Google Scholar, EMBASE, Global Health, The Cochrane Library databases. The authors state that miRNAs are generated by producer cells and then packaged in extracellular vesicles and delivered to other cells by functionally active structures. Extracellular vesicles transport miRNA in a paracrine and endocrine manner. It is emphasized that the mechanism of action of extracellular microRNAs depends on their association with extracellular vesicles. MicroRNAs associated with extracellular vesicles are taken up by cells and act as intracellular microRNAs. MicroRNAs associated and not associated with extracellular vesicles, by interacting with specific receptors, induce the activation of intracellular signaling, most often pro-inflammatory pathways. Extracellular vesicles interact with the membrane of the recipient cell through their surface proteins in a ligand-receptor manner. It is shown that specific proteins of extracellular vesicles, such as major histocompatibility complex class I and class II proteins, transferrin receptors and tetraspanins, induce disruption of some signaling pathways of target cells. Scientists believe that exosomes and ectosomes are absorbed by recipient cells using clathrin-mediated endocytosis, phagocytosis, and/or macropinocytosis. After delivery to target cells, miRNAs regulate the translation of their target genes. Extracellular vesicles circulating in the blood serum of healthy people are believed to have antifibrogenic effects and contain miRNAs that inhibit the activity of hematopoietic stem cells or damaged hepatocytes. Scientists believe that receptor-independent penetration of the hepatitis C virus into hepatocytes can be carried out with the help of exosomes. Exosomal miRNAs and miRNAs not associated with exosomes are able to bind to certain cellular receptors and activate intracellular signaling pathways associated with them.